Initial second-line drug resistance of Mycobacterium tuberculosis isolates from Sudanese retreatment-patients - Muatsim Ahmed Mohammed Adam (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2017)
Setting: Multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB) are a major public health threat. Objective: This study aimed to determine resistance patterns to second line anti-TB drugs (SLDs), and to determine the frequency of extensively drug resistant Mycobacterium tuberculosis (XDR-TB). Design: During the period from July 2009 to July 2010; sputum specimens were collected from TB retreatment patients; isolates were tested for sensitivity to first line anti-TB drugs by the 1% proportion method; MDR strains were tested for second line anti-TB drugs sensitivity by 1% proportion method and by version 1. Hain GenoType MTBDRsl Assay. Results: One hundred and forty three mycobacterial isolates were successfully recovered from a total of 239 specimens (143/239; 59.8%). Fifty six strains were rifampicin resistant (RR); of these 54 were multi-drug resistant (MDR); two were RIF/INH-resistant mycobacterium other than tuberculosis (MOTT). Five of MDR (5/50; 10%) showed resistance to at least one second line drug and one isolate (1/50; 2%) was XDR. The XDR strain was concordantly detected by the two methods. Conclusion: Initial resistance to second line anti-TB drugs among MDR-TB patients is at 10% levels and XDR-TB is prevalent at low levels (2%). Nevertheless; without great efforts from national tuberculosis control program (NTP) this figure can fuel the TB epidemics in Sudan. Keywords: XDR-TB, Pre âXDR, SLDs, Sudan